The implication of mitochondrial dysfunction and mitochondrial oxidative damage in di (2-ethylhexyl) phthalate induced nephrotoxicity in both in vivo and in vitro models. (23rd July 2020) - Ashari, Sorour; Karami, Mohammad; Shokrzadeh, Mohammad; Ghandadi, Morteza; Ghassemi-Barghi, Nasrin; Dashti, Ayat; Ranaee, Mohammad; Mohammadi, Hamidreza
Abstract: Di-(2-ethylhexyl) phthalate (DEHP) and its main metabolite, monoethylhexyl phthalic acid (MEHP), are a serious threat to human and animals' health in the current century. However, their exact mechanism to induce nephrotoxicity is not clear. In the current study, we addressed toxic effects of MEHP and DEHP on embryonic human kidney cells (HEK-293 cell line) and kidney tissue of rats, respectively. In the HEK-293, MTT assay and oxidative stress parameters were measured after treatment with different concentrations of MEHP. For in vivo study, rats were treated with different doses of DEHP (50, 100, 200, 400 mg/kg) via gavage administration for 45 days. The renal function biomarkers (BUN and creatinine) were determined in serum of rats. Mitochondrial toxic parameters including MTT, mitochondrial membrane potential (MMP), mitochondrial swelling, and also oxidative stress parameters were measured in isolated kidney mitochondria. Histopathological effects of DEHP were also evaluated in rats' kidneys. We demonstrated that MEHP induced oxidative stress and cytotoxicity in HEK-293 cells in a concentration dependent manner. The administration of DEHP led to histopathological changes in kidney tissue, which concurred with BUN and creatinine alternations in serum of rats. The results of present study showed a significant mitochondrial dysfunction and oxidative stress confirmed by enhancement of mitochondrial swelling, mitochondrial reactive oxygen species (ROS) and malondialdehyde (MDA), and reduction of MMP and mitochondrial glutathione (GSH). Taken together, this study showed that DEHP/MEHP resulted in mitochondrial dysfunction and oxidative damage, which suggest a vital role of mitochondria in DEHP/MEHP-induced nephrotoxicity. Graphical Abstract: